Salivary IgA versus HIV and Dental Caries - PRADIP KUMAR MANDAL; MALAY MITRA; SONU ACHARYA; CHIRANJIT GHOSH; SUSANT MOHANTY; SUBRATA SAHA (Journal of Clinical and Diagnostic Research, 2016)
Introduction: The inter-relationship of Human Immunodeficiency Virus (HIV) infection and dental caries as well as Salivary Immunoglobulin-A (S-IgA) level appear to remain under explored while a manual and electronic search of the literature was made. Hence, the present study was undertaken to assess the relationship of S-IgA and dental caries status in HIV positive children. Aim: The aim of this study was to find out the relationship of S-IgA antibody with dental caries by measuring the concentration of IgA in saliva of HIV positive and negative children and determine the dental caries status in HIV positive and HIV negative children, which may help in treatment planning and prevention of the same. Materials and Methods: A total of 28 HIV positive children aged between 6-14 years and 28 age matched HIV negative children were included in this study and both samples were randomly selected from the same Non-Governmental Organization (NGO). The HIV status of both these samples was confirmed from their medical records provided by the NGO. Only 2cc of unstimulated saliva was collected from both groups in special tubes coded numerically using the method described by Collins and Dawes and the samples were analyzed to measure the concentration of IgA using commercially available ELISA kit (DRG Diagnostics, Germany). Examination of dental caries was carried out according to WHO criteria (1997) using a flat mouth mirror and CPI probe. Results: In HIV +ve group mean S-IgA level was calculated as 81.61 ± 6.20 µg/ml, mean DMFT was 3.86 ± 3.37, mean deft was 4.75 ± 2.86. In HIV -ve group mean S-IgA level was calculated as 145.57 ± 17.83µg/ml, mean DMFT was 2.54 ± 0.69, mean deft was 2.43 ± 2.01. Strong-ve correlation between S-IgA and DMFT (r = -0.781, t = 6.38, p < 0.001) and negative but Not Significant (N.S.) correlation (r = -0.19, t = 0.99, p > 0.05) between S-IgA and deft was found in HIV +ve group. Strong –ve correlation between S-IgA and DMFT (r = -0.655, t = 4.42, p < 0.001), S-IgA and deft (r = -0.942, t =14.32, p=<0.001) was found in HIV-ve group. Conclusion: This study suggests that the individuals who are suffering from IgA deficiency in general, are more susceptible to dental caries than normal individuals.